RESPONSE OF VARIETIES AND PLANTING DATES ON GROWTH AND YIELD BEHAVIOUR OF LENTIL (LENS CULINARIS MEDIK.) - SEPAT, N.K.; Singh, N.P.; SEPAT, R.N. (Annals of Agricultural Research, 2014)
The field experiment was conducted during rabi 2001-2002 at C2 block of the Crop Research Centre of G.B.P.U.A. & T., Pantnagar, comprising three planting dates (Nov. 5, Nov. 25 and Dec. 15) and six varieties of bold seeded lentil (L4076, DPL 15, DPL 585, DPL 62, Pant L5 and Narendra Massor 1), making 18 combinations were replicated three times in split plot design. Grain and straw yields wereÂ Â significantly influenced by planting dates. Nov. 5 planted crop has 10.75 and 16.75 per cent higher grain yield than Nov. 25 and Dec. 15 planted crop (Table 2). The higher grain yield under Nov. 5 planted crop was due to higher number of pods per plant, number of grains per pod and grain yield per plant. DPL 58, DPL 62 and Pant L5 produced significantly higher yield over NM1, L4076 and DPL 15. While, among these varieties DPL 62 remain outyield . The higher yield of varieties DPL 58, DPL 62 and Pant L5 were due to higher number of pods per plant, number of grains per pod, grain yield per plant and 1000-grain weight.